The transformative power of translation in written texts for connecting a multilingual world - Henríquez Alemán, Oscar Armando (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2024)
In a globalized society such as ours, translation plays a key role in bridging linguistic and cultural divides, fostering communication and facilitating understanding between diverse communities. This study delves into the transformative potential of translation in written texts in the context of a multilingual world, this approach has been presented as part of the activities of the specialization course: Fundamentals of Translation. This study begins by examining the current landscape of translation practices, focusing on the evolving role of translators and the impact of translation in the world. It then provides an overview of the translation process, clarifying its various stages and the techniques employed to ensure linguistic accuracy and cultural resonance. The discussion covers the definition of the translation process, outlining its complexities and challenges, while highlighting the importance of cultural sensitivity and linguistic nuances. Also, the study presents illustrative examples that demonstrate the dynamic nature of translation and its profound cross-cultural impact and promotion of global interconnectedness. Through an exploration of translation techniques and methodologies, it underscores the importance of adaptation and interpretation in conveying meaning across linguistic boundaries. This analysis underscores the transformative power of translation.